Precipitation field from rainfall measurements and rainfall estimates from IPMet’s radars - Borges, Iuri Valério Graciano [UNESP]; Moreira, Demerval Soares [UNESP]; Rozante, José Roberto (Universidade Federal do Rio de Janeiro, 2019)
Precipitation is an essential meteorological variable in several areas of knowledge, such as agriculture, civil defense, energy, etc. However, it is a variable known to be discontinuous both in space and time. To obtain precipitation fields that seek to have an adequate spatial and temporal representation, it would require an extensive distribution of pluviometric stations to achieve a good interpolation of the data. That distribution normally does not occur due to several limiting factors, such as the geography of the study region and economic issues for installation and maintenance of a dense pluviometric network. In order to overcome the lack of rainfall data, this work merged rain gauges data with estimates by meteorological radars creating a precipitation field called “PluRad” covering most of the state of São Paulo, northern Paraná and eastern Mato Grosso do Sul. This product was compared with the IPMet’s (Bauru Meteorological Center) radar precipitation estimates, GPM’s (Global Precipitation Meusurement) product and the MERGE’s product on a 24h’s rainfall at March, 21st 2018, both generated from the rainfall data composition with satellite precipitation estimates. The results showed that PluRad has a better representation of the spatial distribution of precipitation in the analyzed region, mainly due to the high spatial resolution of this product.
Campo de Precipitação Proveniente de Medidas Pluviométricas e Estimativas de Precipitação dos Radares do IPMet
Keywords: Pluviometer; Precipitation field; Weather radar